Learning Fun English During Ramadhan di Panti Asuhan Aisyah Sungayang Kabupaten Tanah Datar - Sari, Dian Purnama (Jurnal Pengabdian UNDIKMA, 2022)
The community service activity aims to teach fun English during Ramadan to foster children at the Aisyah Sungayang Orphanage, Tanah Datar Regency. This activity used the English-speaking training method by ’describing something’ material. Realizing that foster children are still minor, this service activity was carried out through English songs and educational games that make foster children relaxed so that learning English becomes fun. The results of this service activity showed an increase in the enthusiasm of the foster children to learn English. The evaluation results in this activity indicated that foster children felt happy and motivated in using English and expected similar activities in months other than Ramadan. In addition, the increasing vocabulary and foster children’s ability to use English show positive progress due to service activities.